Syndactyly release with skin graft or skin graft substitute: a within-subject controlled trial - Bohn, Deborah C; Price, Jamie N; Novotny, Susan A; Sylvanus, Tonye S; Van Heest, Ann E (The Journal of hand surgery, European volume, 2025)
This study assessed scar healing over a 24-month period after syndactyly release using full-thickness skin autograft or hyaluronic acid matrix skin autograft substitute. A randomized, single-anonymized, within-subject controlled study was used to compare the effectiveness of hyaluronic acid matrix with full-thickness skin autograft, for 40 webs in 18 patients (mean age 1.2 (SD 0.8) years) undergoing syndactyly release. Hyaluronic acid matrix was used on one side of the web and a full-thickness skin autograft on the other. At 12 and 24 months after surgery, healing was assessed using two scar assessment scales and family/surgeon preferences. Results at final follow-up showed that hyaluronic acid matrix and full-thickness skin autograft had no significant differences in scar formation. When compared with full-thickness skin autograft, hyaluronic acid matrix decreases surgical time and has no donor site morbidity; however, there is an open wound for a longer time after operation, with increased requirements for wound care. II.